1976
DOI: 10.1021/ja00440a017
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance and conformational energy calculations of repeat pepetides of tropoelastin: the tetrapeptide

Abstract: Note Added in Proof. After this work was completed and in press, a particularly attractive group theoretical treatment of methyl relaxation has appeared (G. B. Matsen, J . Chem. P h~~s . , in press). This treatment leads to spectral density functions identified with symmetry labels rather than with auto-and cross-correlation. The advantage is to provide a physical interpretation for the pre-and postexponential terms in methyl relaxation behavior characterized by multiple exponentials. Subsequent work from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

1978
1978
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 6 publications
1
15
0
3
Order By: Relevance
“…That is, the conformations with cis Val-Pro peptide bond are restricted to more specified conformational space than those with trans Val-Pro peptide bond (DC, DA, OF, A*F, A*C, A*A, EC, and EA were allowed for Val-Pro portion with trans peptide bond and 11£ < 3 kcal mol -1 ). These results correspond to the results of conformational analysis for Ac-X-Pro-NHMe 12 · 14 with trans or cis peptide bonds, and show that confor- proposed the type II /J-bend structure at ProGly portion in t-Boc-Val-Pro-Gly-Gly-OMe from temperature dependence of NH chemical shift (d<5/dT) in CDCl 3 (with 20% C 6 D 6 ), 6 and HCO-Val-Pro-Gly-Gly-OMe by the NOE measurements in DMSO-d 6 • 7 As mentioned in Results section, the calculated bend probabilities for Ac-Val-Pro-Gly-Gly-NHMe at Pro-Gly portion are 0.171 for type II and 0.429 for type V which is a distorted type II bend, respectively. Total bend probability of type II and type V exceed 0.60.…”
Section: Resultssupporting
confidence: 84%
“…That is, the conformations with cis Val-Pro peptide bond are restricted to more specified conformational space than those with trans Val-Pro peptide bond (DC, DA, OF, A*F, A*C, A*A, EC, and EA were allowed for Val-Pro portion with trans peptide bond and 11£ < 3 kcal mol -1 ). These results correspond to the results of conformational analysis for Ac-X-Pro-NHMe 12 · 14 with trans or cis peptide bonds, and show that confor- proposed the type II /J-bend structure at ProGly portion in t-Boc-Val-Pro-Gly-Gly-OMe from temperature dependence of NH chemical shift (d<5/dT) in CDCl 3 (with 20% C 6 D 6 ), 6 and HCO-Val-Pro-Gly-Gly-OMe by the NOE measurements in DMSO-d 6 • 7 As mentioned in Results section, the calculated bend probabilities for Ac-Val-Pro-Gly-Gly-NHMe at Pro-Gly portion are 0.171 for type II and 0.429 for type V which is a distorted type II bend, respectively. Total bend probability of type II and type V exceed 0.60.…”
Section: Resultssupporting
confidence: 84%
“…they apperar 54 times in bovine elastin (2). Among these the very simple peptide Val-Pro-Gly-Gly has been widely studied as protected monomer (Boc-Val-Pro-Gly-OMe) and polymer by Urry and coworkers (13,14), who evidenced as main structural feature the presence of a type II ~-turn.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that the C"H2 protons of both Gly* and Gly3 in Mets-enkephalin are nonequivalent m Hz0 and (CD,),SO, suggesting that the molecules are inflexible on a chemical shift time scale. Non-equivalence of the C&H2 protons of Gly residues has also been used to support the view that ordered conformations exist in solution, for a tetrapeptide fragment of tropoelastin Boc-Val-ProGly-Gly-OMe [27]. While geminal non-equivalance of the C&H2 protons of Gly3 and the CH3 groups of Aib*, is not conclusive evidence for the presence of I-'lg.2.…”
Section: Resultsmentioning
confidence: 99%